Transcatheter closure of coronary artery fistulas in infants and children: A French multicenter study. Issue 3 (3rd November 2015) - Mottin, Benoît; Baruteau, Alban; Boudjemline, Younes; Piéchaud, François J.; Godart, François; Lusson, Jean‐René; Hascoet, Sebastien; Le Gloan, Laurianne; Fresse, Karine Warin; Guyomarch, Beatrice; Bouzguenda, Ivan; Malekzadeh‐Milani, Sophie; et al.
Abstract : Objectives: The short‐term efficacy and safety of transcatheter closure (TCC) for the management of coronary artery fistulas (CAFs) was investigated in pediatric patients. Background: CAFS are rare with potentially severe complications and their management is still a matter of debate. Percutaneous closure appears to be the treatment of choice in anatomically suitable vessels but limited data are available in the pediatric population. Methods: This retrospective, observational, multicenter, national study included patients under 16 years of age who underwent TCC of a congenital CAF. Patients with additional congenital heart defect were excluded. Results: 61 patients (36 girls, 25 boys) with a median age of 0.6 year [0–15.4] at diagnosis and 3.9 years [0–16] at procedure were included. The CAF was large in 48 patients (79%); it was distal in 23 (38%) and proximal in 22 (36%). Most patients (77%) were asymptomatic at diagnosis. Clinical signs of congestive heart failure were present in seven patients (11%). Perioperative complications included three cases of ST elevation myocardial infarction (exclusively during attempted closure of a distal CAF), three devices migrations, and one case of leg ischemia. One patient died after surgical closure of a large distal CAF that could not be closed by TCC. Follow‐up data were collected for 43 patients (70%) for a median of 91 days [0–4, 824]. The Kaplan‐Meyer estimate for complete occlusion at 2 years was 73 ± 7.6%. Conclusion: TCC in the pediatric population appears to be effective and associated with few complications. © 2015 Wiley Periodicals, Inc.